Age-related changes in the tooth-bone interface area of acrodont dentition in the chameleon - Dosedělová, Hana; Štěpánková, Kateřina; Zikmund, Tomáš; Lesot, Herve; Kaiser, Jozef; Novotný, Karel; Štembírek, Jan; Knotek, Zdeněk; Zahradníček, Oldřich; Buchtová, Marcela (Journal of anatomy, 2016)
Chameleon teeth develop as individual structures at a distance from the developing jaw bone during the pre-hatching period and also partially during the post-hatching period. However, in the adult, all teeth are fused together and tightly attached to the jaw bone by mineralized attachment tissue to form one functional unit. Tooth to bone as well as tooth to tooth attachments are so firm that if injury to the oral cavity occurs, several neighbouring teeth and pieces of jaw can be broken off. We analysed age-related changes in chameleon acrodont dentition, where ankylosis represents a physiological condition, whereas in mammals, ankylosis only occurs in a pathological context. The changes in hard-tissue morphology and mineral composition leading to this fusion were analysed. For this purpose, the lower jaws of chameleons were investigated using X-ray micro-computed tomography, laser-induced breakdown spectroscopy and microprobe analysis. For a long time, the dental pulp cavity remained connected with neighbouring teeth and also to the underlying bone marrow cavity. Then, a progressive filling of the dental pulp cavity by a mineralized matrix occurred, and a complex network of non-mineralized channels remained. The size of these unmineralized channels progressively decreased until they completely disappeared, and the dental pulp cavity was filled by a mineralized matrix over time. Moreover, the distribution of calcium, phosphorus and magnesium showed distinct patterns in the different regions of the tooth-bone interface, with a significant progression of mineralization in dentin as well as in the supporting bone. In conclusion, tooth-bone fusion in chameleons results from an enhanced production of mineralized tissue during post-hatching development. Uncovering the developmental processes underlying these outcomes and performing comparative studies is necessary to better understand physiological ankylosis; for that purpose, the chameleon can serve as a useful model species.
Keywords: ještěři; laser-induced breakdown spectroscopy; zvířata; Tooth Calcification; Tooth; X-Ray Microtomography; čelisti; Jaw; Aging; Lizards; Animals; Dentition; rentgenová mikrotomografie; kalcifikace zubů; dentice; stárnutí; zuby; micro-computed tomography; acrodont dentition; reptiles